2016
DOI: 10.1128/aac.03064-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Polymyxin Monotherapy versus Nonvalidated Polymyxin Combination Therapy versus Validated Polymyxin Combination Therapy in Extensively Drug-Resistant Gram-Negative Bacillus Infections

Abstract: Polymyxins have emerged as a last-resort treatment of extensively drug-resistant (XDR) Gram-negative Bacillus (GNB) infections, which present a growing threat. Individualized polymyxin-based antibiotic combinations selected on the basis of the results of in vitro combination testing may be required to optimize therapy. A retrospective cohort study of hospitalized patients receiving polymyxins for XDR GNB infections from 2009 to 2014 was conducted to compare the treatment outcomes between patients receiving pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Antagonism was observed in all polymyxin B-based combinations except polymyxin B plus tigecycline against one or more CREC strains. This finding suggested that the empirical selection of polymyxin B-based combinations can be counterproductive and emphasized the importance of in vitro testing in guiding the selection of effective combinations (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonism was observed in all polymyxin B-based combinations except polymyxin B plus tigecycline against one or more CREC strains. This finding suggested that the empirical selection of polymyxin B-based combinations can be counterproductive and emphasized the importance of in vitro testing in guiding the selection of effective combinations (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…For colistin and amikacin, total concentrations were used because either total or free concentrations have been shown to be important for pharmacokinetics/pharmacodynamics (PK/PD) by several different reports ( 10 13 ). One of the colistin-based combination therapies was used as a positive control because this is an important currently available option for combatting carbapenem-resistant Gram-negative pathogens, including MBL producers ( 14 , 15 ). As the isolates used in this study were resistant to multiple classes of antibiotics, colistin-amikacin combination therapy was evaluated, although these isolates were resistant to amikacin.…”
Section: Textmentioning
confidence: 99%
“…The HFIM is used to simulate the pharmacokinetics and pharmacodynamics of the tested drugs singly and in combination with time-kill studies. Thirty patients with drug-resistant Gram-negative bacterial infections were managed with combination antimicrobials based on synergistic drug testing with lower mortality rate compared to controls (Cai et al, 2016a ). Further prospective studies are required to further correlate HFIM testing or other antimicrobial synergy testing methodologies with clinical outcomes.…”
Section: Laboratory Testing and Treatment In The Era Of Carbapenem Rementioning
confidence: 99%